Photo-crosslinked GelMA loaded with dental pulp stem cells and VEGF to repair critical-sized soft tissue defects in rats - Matheus, Henrique R. [UNESP] (2023)
Background: Tissue engineering of skin and mucosa is essential for the esthetic and functional reconstruction of individuals disfigured by trauma, resection surgery, or severe burns while overcoming the limited amount of autograft and donor site morbidity. Purpose: We aimed to determine whether a combination of Gelatin-methacryloyl (GelMA) hydrogel scaffold alone or loaded with either dental pulp stem cells (DPSCs) and/or vascular endothelial growth factor (VEGF) could improve skin wound healing in rats. Materials and Methods: Four 10 mm full-thickness skin defects were created on the dorsum of 15 Sprague-Dawley rats. The wounds were treated with GelMA alone, GelMA+DPSCs, or GelMA+DPSCs+VEGF. Unprotected wounds were used as controls. Animals were euthanized at 1-, 2-, and 4 weeks post-surgery, and the healing wounds were harvested for clinical, histological, and RT-PCR analysis. Results: No signs of clinical inflammation were observed among all groups. Few and sparse mononuclear inflammatory cells were observed in GelMA+DPSCs and GelMA+DPSCs+VEGF groups at 2 weeks, with complete epithelialization of the wounds. At 4 weeks, the epidermis in GelMA+DPSCs and GelMA+DPSCs+VEGF groups was indistinguishable from the empty defect and GelMA groups. The decrease in cellularity and increase in density of collagen fibers were observed over time in both GelMA+DPSCs and GelMA+DPSCs+VEGF groups but were more evident in the GelMA+DPSCs+VEGF group. The GelMA+DPSCs+VEGF group showed a higher expression of the KER 10 gene at all time points compared with the other groups. Expression of Col1 A1 and TGFβ-1 were not statistically different over time neither among the groups. Conclusion: GelMA scaffolds loaded with DPSCs, and VEGF accelerated the re-epithelialization of skin wounds.